2022
DOI: 10.32604/cmc.2022.025629
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Convolutional Neural Network Model for Malaria Cell Images Classification

Abstract: Infectious diseases are an imminent danger that faces human beings around the world. Malaria is considered a highly contagious disease. The diagnosis of various diseases, including malaria, was performed manually, but it required a lot of time and had some human errors. Therefore, there is a need to investigate an efficient and fast automatic diagnosis system. Deploying deep learning algorithms can provide a solution in which they can learn complex image patterns and have a rapid improvement in medical image a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…To boost the results obtained, we used the confusion matrix to determine the accuracy, recall, precision, and the harmonic mean of precision and sensitivity, which is called the F1score as shown in Eqs. ( 7)-( 10) [37,38].…”
Section: Resultsmentioning
confidence: 99%
“…To boost the results obtained, we used the confusion matrix to determine the accuracy, recall, precision, and the harmonic mean of precision and sensitivity, which is called the F1score as shown in Eqs. ( 7)-( 10) [37,38].…”
Section: Resultsmentioning
confidence: 99%
“…The input to the network was decreased thanks to the author's usage of the PCA for dimensional reduction. The research [10] indicates that the new result from the ESC ST-T database exceeds the prior one. In [11] They employed various kinds of multilayer neural networks as classi ers to identify the two types of ECG patterns.…”
Section: Ecg Classi Cation Techniquesmentioning
confidence: 85%
“…The outcomes of this research have been contrasted with other neural network architectures to determine which neural network structure is most effective for classifying types of arrhythmias. To identify ischemia arrhythmia episodes in the ECG data, a neural network was put into use [10]. The input to the network was decreased thanks to the author's usage of the PCA for dimensional reduction.…”
Section: Ecg Classi Cation Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…The results demonstrated that Faster R-CNN is the most well-trained model with an average precision of over 0.94 [29]. For automatic diagnosis of malaria, stacked CNN [30,31] and an ensemble of residual networks [32] were recently used, with accuracy rate of 99.96% and 98.08%, respectively.…”
Section: Literature Reviewmentioning
confidence: 99%